Pemasaran Sosial Program Peduli Gizi Balita oleh Puskesmas Bojonggede Bogor - Immasyari Amruroh; Diana Anggraeni (CoverAge: Journal of Strategic Communication, 2017)
Malnutrition’s problem is still one of the problems in Indonesia. Puskesmas Bojonggede as a health service unit in Bojonggede sub-district has made efforts to overcome by providing information about balanced nutrition informatively. Through the social marketing Care for Nutrition Toddlers Puskesmas Bojonggede intends to persuade the target audience and increase mother awareness in terms of giving nutritious food on her toddler. This study aims to describe the communication process on the social marketing of Nutrition Care of Toddlers conducted by Bojonggede Public Health Center in RW 06 Village Rawa Panjang, Bogor. Concept in this research consists of social marketing concepts, social change campaigns, and social marketing communications. This research using a qualitative descriptive research to give a detailed description about communication process on social marketing of Child Nutrition Care at RW 06 Village Rawa Panjang, Bogor. Results of this study indicate that the communication process on the social marketing of Nutritional Care of Toddlers can improve the knowledge of target adopter on balanced nutrition. But it has not been able to shape the awareness of adopter targets to voluntarily provide nutritious food for their children. This is due to the limited means and location of information dissemination on balanced nutrition, target adopter economic factors, and preoccupation of each target adopter.